(untitled) (JURNAL ADMINISTRASI PUBLIK, 2020)
Service is to help to provide everything that others need including buyers. Service can be given to others as a help that others themselves need. Which with that help can help others themselves. Which with that help can help others to be able to solve the problem. Professional public service means to characterize the accountability and responsiveness of the service provider. In order to achieve public service, it is necessary to understand the principles of good public service namely, simplicity, clarity, certainty, time, accuracy and comfort. The above principles of public service must be adapted to the development and needs of the community in realizing excellent public services in accordance with the demands and expectations of the community. The implementation of public services is, the state’s efforts to meet the basic needs, and civil rights of every citizen for the goods, services, and administrative services provided by public service providers. Key words: quality, of public, service.